2020
DOI: 10.1097/md.0000000000021584
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness comparisons of different Chinese herbal injection therapies for acute cerebral infarction

Abstract: Background: Acute cerebral infarction (ACI) has a high incidence, recurrence rate, and mortality. Chinese herbal injections (CHIs) are widely used in the substitution therapy of ACI. Due to the lack of randomized trials comparing the efficacy of various injections directly, it is still difficult to judge the relative efficacy. Therefore, we intend to conduct a network meta-analysis to evaluate the benefit among these CHIs. Methods: According to the retrieval strategies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…After evaluating, all studies achieved a score no less than 3, which indicating that all studies had good methodological quality. The summarized content for each study (13,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) is shown in Table 1.…”
Section: Literature Search Results and Quality Evaluationmentioning
confidence: 99%
See 4 more Smart Citations
“…After evaluating, all studies achieved a score no less than 3, which indicating that all studies had good methodological quality. The summarized content for each study (13,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) is shown in Table 1.…”
Section: Literature Search Results and Quality Evaluationmentioning
confidence: 99%
“…The 12 studies (13,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) that reported the effective rate were analyzed under a random effect model. Meta-analysis showed a significantly higher overall effective rate in safflower yellow group compared with that in the control group (RR =1.24, 95% CI: 1.19, 1.30, P<0.00001) (Figure 2) (30).…”
Section: Total Effective Rate Of Safflower Yellow Pigmentmentioning
confidence: 99%
See 3 more Smart Citations